2012
DOI: 10.1673/031.012.6301
|View full text |Cite
|
Sign up to set email alerts
|

Lepidopterans as Potential Agents for the Biological Control of the Invasive Plant,Miconia calvescens

Abstract: This work investigated eight species of Lepidoptera associated with Miconia calvescens DC. (Myrtales: Melastomataceae) in Brazil, including six defoliators, Salbia lotanalis Druce (Lepidoptera: Pyralidae), Druentia inscita Schaus (Mimallonidae), Antiblemma leucocyma Hampson (Noctuidae), three Limacodidae species, a fruit borer Carposina cardinata Meyrick (Carposinidae), and a damager of flowers Pleuroprucha rudimentaria Guenée (Geometridae). Based on host specificity and the damage caused to plants, S. lotanal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Although preliminary, our tests provide further ev idence that S. lotanalis has a host range restricted to Melastomataceae (Morais et al 2012). Some of the Miconia spp.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Although preliminary, our tests provide further ev idence that S. lotanalis has a host range restricted to Melastomataceae (Morais et al 2012). Some of the Miconia spp.…”
Section: Discussionmentioning
confidence: 67%
“…We found that S. lotanalis was relatively easy to rear in the laboratory on potted M. calvescens, an important consideration for a potential biocontrol agent. Morais et al (2012) found that S. lotanalis could also be reared on M. calvescens leaves in plastic bags.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of neotropical arthropods and pathogens have been evaluated as potential biological control agents of M. calvescens in recent years, but so far only a fungal pathogen has been released in Hawaii and Tahiti (Killgore 2002, Picanç o et al 2005, Badenes-Perez et al 2008, Hanson et al 2010, Conant et al 2013). Among insects evaluated as potential agents, Salbia lotanalis Druce (Lepidoptera: Crambidae), whose larvae tie leaves producing large leaf rolls within which they feed, has been the subject of biology and hostspeciÞcity studies in Brazil (Morais et al 2010(Morais et al , 2012 and Costa Rica (Castillo 2009, Castillo et al 2014. The insect has Þve larval instars and completes one generation in 60 Ð90 d (Morais et al 2010, Castillo et al 2014.…”
mentioning
confidence: 99%